Systemic intervention in creative managing problems in enterprises - Petrovic, Slavica P. (Journal of Business Economics and Management, 2015)
The main purpose of this paper is to critically reassess the theoretical foundations and the methodological development of Systemic Intervention (SI) – as a new paradigm, based on theoretical and methodological pluralism – in order to determine the conditions, the ways and the results of its application in managing complex problems in enterprises. The employed instrumentarium is critical systems thinking, with its commitments to the critical awareness of the strengths and weaknesses of each research instrument for tackling problems in enterprises, the improvement of managing complex problems, and pluralism – respecting different interpretations of problem situations and enabling the combined use of research instruments. The main finding is that SI can underpin the process of structuring complex management problems in enterprises in a scientifically based and practically useful manner. In a scientific sense, the important implication of the conducted research is that it contributes to holistic understanding, conceptualizing and managing problem situations in enterprises. The relevant practical implication for managers is that – through a critical use of the SI methodology – they can creatively enhance the strategic management process in enterprises.